THE EFFECTIVENESS OF MNEMONIC TO TEACH VOCABULARY VIEWED FROM STUDENTS’ CREATIVITY - Dhian Marita Sari; Zailani; Retty Aureli (At Turots: Jurnal Pendidikan Islam, 2020)
To be able to enhance and support of English skills, learners previously have to master vocabulary. In contrast, students consider and see English as a foreign language that is not understood, unused, and feared. Beside, they easily forget the newly learned words that have been taught. Those are mostly problem that are faced of students in learning vocabulary. The objectives of this research are finding out whether: (1) mnemonic is more effective than direct instruction to teach vocabulary; (2) the students having high creativity have better vocabulary mastery than those having low creativity; (3) there is an interaction between teaching techniques and creativity in teaching vocabulary. This research was an experimental study.